Self Balancing Unicycle Controlled by Using Arduino - Muhammad Ikram, Mohd Rashid; Mohd Khomaini, Mohd Noor; Suliana, Ab Ghani (2016)
This paper presents an exploratory evaluation on how to build an electric unicycle vehicle controlled by using the Arduino board development. For electric unicycle, it will move forward when the user lean their body forward and vice versa. The discussion is majorly includes the way to achieves the stability with the help of the latest electronic sensor technology called gyroscope and accelerometer. The gyroscope will read any changing of angle while the accelerometer is used to detect any changing of acceleration the unicycle exerts. As both sensors tends to produce noise and disturbance, this thesis also discussed the use of Kalman Filter that will combine the data from both sensors to produce a better and accurate data. All the information are then processed by Arduino board controller that acts as the brain of the unicycle system. The Arduino IDE software is used to write the coding to determine the unicycle action based on the information received. The data outputs then are analyzed by displaying them on “Serial Chart” software that will creates a line chart based on serial monitor set on Arduino IDE. This software helps the researcher to observe any unwanted noise in the data and perform a correction upon the problem. Moreover, the discussion are also includes on how to use “SketchUp 8” software to design the unicycle body frame. All the consideration in the sketching then are used for real hardware making that used high power electrical machine. So, there will be also the discussion on mechanical works that includes a series of drilling, grinding, cutting, sanding and others process. By taking all the measurement, the experimental results confirm that the resulting system meets the design goal which to design an electric unicycle controlled by using Arduino and to create a stable electric unicycle with the latest technology.